(untitled) (The Strategic Review for Southern Africa, 2020)
Twenty years of democratic South Africa inspires many scholars to look back, reflect on the achievements and failures and take stock of the current situation, maybe even to cast a view on possible future scenarios. This issue of the Strategic Review for Southern Africa is one of many efforts to engage with social realities in the context of a post-apartheid society; a society, where controlled change with the negotiated transition to regular democratic elections in a multi-party pluralist setting resulted to some extent in changed control. We are confronted with socio-economic, as well as political realities affected by and facing the challenges of structural legacies. The transitions and transformations documented re-alignments within a social and political framework, but often rather modified instead of transcended the previous systemic boundaries. The lack of fundamental shifts towards a genuinely people-centered development stands in strong contrast to the new elite policy and the relative privileges secured by its beneficiaries in the echelons of state and administration and the private sector. The emerging trends have been dubbed by some scholars as the 'limits to liberation'. The aim of this special issue is to contextualise the efforts, hopes, aspirations, declared goals and the setbacks, measured against the expectations with regard to different sectors, and cross cutting issues pertinent to contemporary South African society.